Evolution of the otter population (Lutra lutra; Linnaeus, 1758) and water treatment in the Segura River Basin (Spain) - Ballesteros Pelegrín, Gustavo A.; Salmerón Rodríguez, María E.; Pastor González, Alejo (Anales de Geografía de la Universidad Complutense, 2021)
The otter is a species which suffered a great regression in the Segura basin in the second half of the 20th century, going through a critical period in the 1980s, above all due to hunting and the deterioration of water quality due to the increase in population, agricultural and industrial activities, in a scenario with a deficit of purification systems. The three otter samples taken in 1984-1985, 1994-1995 and 2005-2006 in the Segura basin are analysed, reflecting an expansion of its distribution area, especially in the last period, with the improvement of water quality due to the progressive implementation of treatment plants with the sanitation and waste water treatment plan in the Region of Murcia, going from being a rare species to occupying a large part of the basin in a stable manner in thirty years. La nutria es una especie que sufrió una gran regresión en la cuenca del Segura en la segunda mitad del siglo XX, atravesando un periodo crítico en la década de 1980, sobre todo por la caza y el deterioro de la calidad del agua por el aumento de la población, actividades agrícolas e industriales, en un escenario con déficit de sistemas de depuración. Se analizan los tres muestreos de nutria realizados en 1984-1985, 1994-1995 y 2005-2006 en la Cuenca del Segura, que refleja una ampliación de su área de distribución, sobre todo en el último periodo, con la mejora de la calidad del agua por la progresiva implantación de depuradoras con el plan de saneamiento y depuración de aguas residuales en la Región de Murcia, pasando en treinta años de ser una especie rara a ocupar de forma estable gran parte de la cuenca. La loutre est une espèce qui a subi une grande régression dans le bassin du Segura dans la seconde moitié du XXe siècle, en passant par une période critique dans les années 80, surtout à cause de la chasse et de la détérioration de la qualité de l'eau due à l'augmentation de la population, des activités agricoles et industrielles, dans un scénario de déficit de systèmes d'épuration. Les trois ...